Fears and Perception of the Impact of COVID-19 on Patients With Lung Cancer: A Mono-Institutional Survey - Catania, Chiara; Spitaleri, Gianluca; Del Signore, Ester; Attili, Ilaria; Radice, Davide; Stati, Valeria; Gianoncelli, Letizia; Morganti, Stefania; de Marinis, Filippo (Frontiers in Oncology, 2020)
Abstract On February 2020 Italy become one of the first countries in the world plagued by the SARS-CoV-2 pandemic, COVID-19, so on March 2011 the Italian government decreed a lockdown for the whole country which overturned communication systems, hospital organizations, the access to patient cares, in particular for cancer patients. Therefore, our Thoracic Oncology Division, considering the greatest risk of lung cancer patients due to the fragility of the respiratory system, reorganized patient access in order to reduce the risk of contagion and at the same time encourage the continuation of treatments. So far, our staff contacted all our patients to ascertain their feelings, symptoms of COVID-19, safety measures taken communicating to them any changes in treatment planning. To better understand the fears and expectations of patients during the pandemic period, from April to May 2020 we interviewed 156 patients with lung cancer, treated at our Division. Patient were classified by age, sex, comorbidity, stage of disease, prior and type of treatments. The survey showed that during the pandemic period some patients experienced fear of COVID-19, in particular women (55% vs 33%), patients with comorbidities (24% vs 9%), patients who had already received prior insult (radiotherapy or surgery) on the lung (30% vs 11%). In addition, the patients who received oral treatment at home or to whom intravenous treatment was delayed, experienced a sense of relief in 90% and 72% respectively. However, only 21% of patients were more afraid of COVID-19 than their cancer, in particular patients with long-term (> 12 months) vs short-term cancer diagnosis (28% vs 12.5%, respectively). On the other hand, the quarantine period or even just the lockdown period, worsened the quality of life of some patients (40%), especially for patients in oral treatment (47%). Therefore, these data demonstrate how much lung cancer patients are afraid of their disease, more than a world pandemic. On the other hand, this interview also indirectly highlights the major guiding principle of the clinician in the correct management of the patient's expectations of his illness and treatments, but especially of the patient's fears.